2014
DOI: 10.1590/1678-6958
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of the consumers of the Federal District - Brazil - to purchase beef meat with certification of origin

Abstract: Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…Lu et al (2016) completed a research on consumer preferences for traceable pork in China by using a choice-based conjoint analysis and a multinomial logit model. The findings of the study showed that preference and demand for traceable pork were highly influenced by consumers' age, income level and education level, which were similar to the results of other studies, such as Feng et al (2009), Rigueira et al (2014), andWu et al (2012). Lu et al (2016) found that four aspects, traceability information, certification of traceability information, the appearance of the meat and price, were also responsible to set consumer's demand for traceable pork.…”
Section: Literature Reviewsupporting
confidence: 82%
See 2 more Smart Citations
“…Lu et al (2016) completed a research on consumer preferences for traceable pork in China by using a choice-based conjoint analysis and a multinomial logit model. The findings of the study showed that preference and demand for traceable pork were highly influenced by consumers' age, income level and education level, which were similar to the results of other studies, such as Feng et al (2009), Rigueira et al (2014), andWu et al (2012). Lu et al (2016) found that four aspects, traceability information, certification of traceability information, the appearance of the meat and price, were also responsible to set consumer's demand for traceable pork.…”
Section: Literature Reviewsupporting
confidence: 82%
“…The explanatory variables from four categories, namely 1) demographic variables 2) socio-economic variables 3) attitudinal variables and 4) knowledge variables were chosen for the model. From previous studies, the demographic factors, including gender, age, and family size, and socioeconomic variables, such as education level and family income, were taken (see, e.g., Haghiri 2014, Rigueira et al 2014). In addition to the socio-economic and demographic factors, this study also focused on a number of behavioral factors and knowledge variables and hypothesized that they were relevant to identifying consumers' WTP a premium price for buying farm-raised traceable salmon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barcellos et al (2012) destacan que la mayoría de la población está dispuesta a pagar más por una carne con trazabilidad y consideran oportuno este mercado para ser utilizado como una herramienta para diferenciación de los productos cárnicos. Además, si se trata de un producto que garantice la calidad, los consumidores estarían dispuestos a pagar más (Vasconcelos Queiroz et al, 2014;Rigueira, Lopes, Pascoti Bruhn, Rodrigues & Faria, 2014). Maysonnave et al (2014) y Brandão et al (2012) constatan que 87,8% y 65,4% de los consumidores nunca consumieron carne con algún sello de calidad específica.…”
Section: Resultados Y Discusiónunclassified